Cervical myelomeningocele. Case report - Injante-Bustamante, Rossie Thais (2023)
Myelomeningocele is the most frequent form of spinal dysraphism, it represents a congenital anomaly of posterior neuropore closure and its cervical location is rare. The clinical case of a newborn born at the Perinatal Maternal Institute, who presented cervical myelomeningocele with neurological deterioration from birth and a karyotype with Robertsonian translocation, is presented.